Leveraging E-Marketing for Enhancing Customer Knowledge Management: A Systematic Review of Tourism Strategies in the Saudi Arabian Context - Ghonim, Adel; Awad, Abdelrehim (Journal of Ecohumanism, 2025)
Purpose: This study explores the intersection of e-marketing and customer knowledge management (CKM) within the context of the Saudi Arabian tourism sector. It aims to analyze how e-marketing tools, particularly social media, enhance customer engagement and knowledge management practices to achieve sustainable tourism growth in line with Vision 2030. Design/Methodology/Approach: A systematic literature review approach was employed, focusing on peer-reviewed articles published between 2015 and 2024. The study adhered to PRISMA guidelines for article selection, and a total of 36 research papers were thoroughly analyzed. The literature was categorized into three main themes: CKM frameworks, e-marketing strategies in tourism, and social media's role in customer engagement and knowledge transfer. Findings: The review indicates that e-marketing, especially through social media platforms, significantly enhances CKM by facilitating real-time customer interactions, feedback loops, and data gathering. These tools help overcome traditional CKM challenges, such as knowledge transfer and storage, particularly in the tourism context. Saudi Arabia’s unique cultural and economic environment presents specific opportunities and challenges in implementing these strategies effectively. Originality/Value: This paper is one of the first to comprehensively analyze the role of e-marketing in CKM within the Saudi tourism sector. It proposes a structured framework for integrating digital strategies with CKM to optimize customer engagement and service delivery. The findings offer actionable insights for policymakers and tourism managers on leveraging e-marketing tools to achieve competitive advantage and sustainable growth